LEARNING WRITING IN PRIMARY SCHOOL (Qualitative Study- Ethnography in SD Islam Jerapah Kecil Jakarta Timur) - Yarmi, Gusti (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2017)
The aims of this study is to determine the understanding of the application of learning to writing in Islamic Primary School Jerapah Kecil. This study is a qualitative study using ethnographic methods by Spredly models. This study was conducted in March-July 2013. The results of this study indicate that the teaching of writing in Islamic Primary School jerapah kecil has a unique associated with writing learning objectives, which expects students have writing skills through the practice of writing contextually and directing the students how student happy and loved to writing. Through writing activities teachers can instill a positive attitude to the students. In this study it was found that the approach used in the teaching of writing in addition to using the communicative approach and whole language is also very good on student-centered learning. Writing skills of students trained through various activities at the school. Writing activities performed in the morning activities, the process of learning activities and activities by school program. Writing a journal is a routine activity conducted in the morning activities in order to train skilled student and enjoys writing. Various program activities outside of school in order to stimulate various aspects of development and potential students, including writing. Assessment that teachers do, not just results-oriented, but also the process. Then the aspects that not only the cognitive aspects but also aspects of the attitude or character cultivation. Utilizing a variety of learning resources one museum as a learning resource writing to develop positive attitudes in students through writing activities. Penelitian ini bertujuan untuk mengetahui pemahaman mengenai penerapan pembelajaran menulis di Sekolah Dasar Islam Jerapah Kecil. Penelitian ini adalah penelitian kualitatif dengan menggunakan metode etnografi model Spredly. Penelitian ini dilaksanakan pada bulan Maret-Juli 2013. Hasil penelitian ini menunjukkan bahwa pembelajaran menulis di Sekolah Dasar Islam Jerapah Kecil memiliki keunikan yang berkaitan dengan tujuan pembelajaran menulis, yaitu mengharapkan siswa memiliki keterampilan menulis melalui praktek menulis secara kontekstual dan lebih mengarahkan pada siswa bagaimana siswa senang dan gemar menulis. Melalui kegiatan menulis guru dapat menanamkan sikap positif pada diri siswa. Dalam penelitian ini ditemukan bahwa pendekatan yang digunakan dalam pembelajaran menulis selain menggunakan pendekatan komunikatif dan whole language juga sangat ditekankan pada pembelajaran yang berpusat pada siswa. Keterampilan menulis siswa dilatih melalui berbagai kegiatan yang ada di sekolah. Kegiatan menulis dilakukan pada kegiatan pagi, pada proses kegiatan pembelajaran dan kegiatan program sekolah. Menulis jurnal merupakan kegiatan rutin yang dilakukan pada kegiatan pagi dalam rangka melatih siswa terampil dan gemar menulis. Memprogramkan berbagai kegiatan di luar sekolah dalam rangka menstimulasi berbagai aspek perkembangan dan potensi siswa termasuk menulis. Penilain yang dilakukan guru tidak hanya berorientasi pada hasil tetapi juga proses. Kemudian aspek yang dinilai tidak hanya aspek kognitif namun juga aspek sikap atau penanaman karakter. Memanfaatkan sumber belajar yang bervariasi salah satunya museum sebagai sumber belajar menulis yang dapat mengembangkan sikap positif pada siswa melalui kegiatan menulis.